(untitled) (Research, Society and Development, 2022)
In the semiarid region, the use of saline water for irrigation in the production of forage for livestock is an alternative that can contribute to food security. The work aims to evaluate the effect of irrigation with saline water and the use of goat manure on mycorrhizal symbiosis and soil carbon contents in a semiarid area cultivated with cactus forage. The effects of water depths (0, 370, 520 and 700 mm), associated with four doses of goat manure (0, 15, 30 and 45 t ha-1), on the carbon content in the soil, were evaluated. in microbial biomass, basal respiration, the number of spores of arbuscular mycorrhizal fungi (AMF) in the soil and root colonization by AMF. The amount of saline water added in different samples did not affect the evaluated parameters. Fertilization with goat manure increased soil C content and microbial respiration, but reduced palm root colonization by AMF.